Peningkatan Kreativitas melalui Penerapan Pembelajaran Team Based Project pada Mata Kuliah Desain Komunikasi Visual - Sigit Indrawijaya; Ade Perdana Siregar (Universitas Batanghari Jambi, 2022)
Education currently has a goal to build students on intelligence abilities in learning so that students can be able to create solutions to problems around them. The most important component in contextual learning to be successful in dealing with a complex world is creativity. Project-based learning models are more effective in increasing students' creativity compared to conventional learning. The purpose of this study was to examine the effect of applying project-based learning with the Team Based Learning (TBL) method in increasing student creativity in the visual communication design course. The research method used is descriptive as an evaluation stage. Descriptive analysis is used to describe as an evaluation with creativity qualifications for students who are in charge of visual communication design courses. Project-based learning models in visual communication design courses using the team-based project method can increase student creativity, this is very much needed in today's conditions. Promotions currently tend to be done digitally so that creativity is very supportive to create consumer attraction in conducting marketing communications.